Investigation of Preliminary Dilution Process for Return Water before Discharge into Water Body - Vadym Orel; Oksana Matsiyevska; Bohdan Pitsyshyn; Vlad Drogan (Energy Engineering and Control Systems)
One of the methods to intensify the initial dilution process of return water from a sewage treatment facility is to disconnect individual diffuser-type return water discharge devices. It is proposed to perform pre-dilution of return water in a mixer with water from the receiving water body into which they are discharged. The return water should pass into the mixer through the water discharge devices (nozzles) of the distribution pipeline. Empirical research methods were used in this work. The experiments were conducted using the model water. In the hydraulic flume, the water flow was in a calm state, while in the distribution pipeline, the flow regime was turbulent. An increase in return water dilution by 12.2% was achieved by reducing the number of nozzles in the distribution pipeline from seven to four. This confirms the possibility of intensifying the return water dilution by avoiding the interaction between the jets emerging from the discharge devices in the distribution pipeline. If necessary, it is recommended to use the ways of increasing the flow rate of return water from the discharge devices.